MONITORING KUALITAS UDARA UNTUK MENGUKUR KONSENTRASI PARTIKEL UDARA BERBASIS INTERNET OF THINGS - Setiawan, Dimas; Abdurrahman (JURNAL TELISKA, 2025)
Increasing air pollution has become one of the most pressing environmental issues of the modern era, with significant impacts on human health and ecosystems. This research presents an Internet of Things (IoT)-based air quality monitoring system designed to measure concentrations of PM2.5 particles, carbon monoxide (CO), and nitrogen dioxide (NO2). This system uses sophisticated sensors connected via an IoT network to collect real-time air quality data from various locations. The data obtained is then sent to a cloud platform for analysis and visualization using a web-based application. This methodology enables continuous monitoring and widespread mapping of air quality with high accuracy. The results of the tests show that this system can provide accurate and timely information on air pollution levels, which can be used to increase public awareness, optimize environmental policies, and minimize health risks. It is hoped that this research can contribute to the development of more effective and responsive air monitoring technology in the future.